THE ACCEPTABLE COMPACTION ZONE CRITERIA BASED ON HYDRAULIC CONDUCTIVITY FOR A COMPACTED MIXTURE OF RESIDUAL SOIL WITH BENTONITE AS A SOIL LINER (Jurnal Teknologi (Sciences & Engineering), 2025)
The significant criteria for compacted clay liner in landfill construction are the compaction characteristics and hydraulic conductivity value. The primary parameter for designing an efficient soil liner is ensuring a hydraulic conductivity value below 1x10-9 m/s to prevent contaminated seepage into the aquifer. Therefore, the compaction criteria are crucial in controlling the construction of hydraulic barriers for liners. In this study, laboratory testing such as permeability tests at varying compaction energies, were carried out on a blend of residual soil and bentonite. The aim was to establish an acceptable compaction zone based on the allowable hydraulic conductivity value and to outline suitable design considerations for compacted residual soil mixed with bentonite as a soil liner. The design parameters investigated included hydraulic conductivity at different compaction efforts. A comparison was made between traditional, common, and modern approaches to ensure construction quality assurance for compacted soil liners mixed with bentonite. The results indicated that all methods, traditional, common, and modern, successfully met the design objectives for hydraulic conductivity, creating acceptable compaction zones on the compaction plane curve. These acceptable zones for the mixture of residual soil with bentonite align with the lower bound limit of the compaction optimum line, with the shapes of the shaded zones influenced by the soil's moisture content and compaction characteristics.